Forecasting ECB policy rates with different monetary policy rules - Ansgar Belke; Jens Klose (RWI - Leibniz-Institut für Wirtschaftsforschung, 2019)
This article compares two types of monetary policy rules - the Taylor-Rule and the Orphanides-Rule - with respect to their forecasting properties for the policy rates of the European Central Bank. In this respect the basic rules, results from estimated models and augmented rules are compared. Using quarterly real-time data from 1999 to the beginning of 2019, we find that an estimated Orphanides-Rule performs best in nowcasts, while it is outperformed by an augmented Taylor-Rule when it comes to forecasts. However, also a no-change rule delivers good results for forecasts, which is hard to beat for most policy rules. – – In diesem Artikel vergleichen wir zwei Arten geldpolitischer Regeln - die Orphanides- und die Taylor-Regel - hinsichtlich ihrer Prognosefähigkeit des Leitzinses der Europäischen Zentralbank miteinander. Es werden die Standardregeln, geschätzte Regeln und erweiterte Regeln miteinander verglichen. Für Quartalsdaten in Echtzeit im Zeitraum 1999 bis Anfang 2019 ergibt sich, dass eine geschätzte Orphanides-Regel am geeignetsten im Nowcast ist, während diese Regel schlechter als erweiterte Taylor-Regeln im Falle von Zinsprognosen abschneidet. Zudem liefert eine Regel, die keine Änderungen des Zinssatzes annimmt, ebenfalls gute Vorhersagen, die für die meisten geldpolitischen Regeln schwer zu schlagen sind.
Keywords: E43; E52; E58; C53; 330; Taylor-Rule; Orphanides-Rule; monetary policy rates; forecasting; European Central Bank